Pengembangan Sistem Administrasi Surat Masuk dan Keluar Berbasis Desktop dan Mobile (Studi Kasus Politeknik Negeri Cilacap) - Wily Riezkiadi; Nur Wahyu Rahadi; Riyadi Purwanto (P3M Politeknik Negeri Indramayu, 2016)
Information technology has a significant role in the education field. One of the critical roles of information technology is in the form of managing the incoming and outgoing mails. State Polytechnic of Cilacap as a higher education institution feels this role. In this research, the author intends to develop the information systems of the incoming and outgoing mails which is accessible for mobile. The development of this information system implements the waterfall process model. The result of the user testing showed that 75% of the users responded it as excellent, 17% of the users responded it as good, and the rest responded it as enought.